Cardiovascular diseases in Africa in the twenty-first century: Gaps and priorities going forward - Minja, Neema W.; Nakagaayi, Doreen; Aliku, Twalib; Zhang, Wanzhu; Ssinabulya, Isaac; Nabaale, Juliet; Amutuhaire, Willington; de Loizaga, Sarah R.; Ndagire, Emma; Rwebembera, Joselyn; Okello, Emmy; Kayima, James (Frontiers in Cardiovascular Medicine, 2022)
In 2015, the United Nations set important targets to reduce premature cardiovascular disease (CVD) deaths by 33% by 2030. Africa disproportionately bears the brunt of CVD burden and has one of the highest risks of dying from non-communicable diseases (NCDs) worldwide. There is currently an epidemiological transition on the continent, where the high burden of NCDs is projected to outpace communicable diseases within the current decade. Unchecked increases in CVD risk factors have contributed to the growing burden of three major CVDs - hypertension, cardiomyopathies, and atherosclerotic diseases- leading to devastating rates of stroke and heart failure. The highest age standardized disability-adjusted life years (DALYs) due to hypertensive heart disease (HHD) were recorded in Africa. The contributory causes of heart failure are changing – whilst HHD and cardiomyopathies still dominate, ischemic heart disease is rapidly becoming a significant contributor, whilst rheumatic heart disease (RHD) has shown a gradual decline. In a continent where health systems are traditionally geared towards addressing communicable diseases, several gaps exist to adequately meet the growing demand imposed by CVDs. Among these, high-quality research to inform interventions, underfunded health systems with high out-of-pocket costs, limited accessibility and affordability of essential medicines, CVD preventive services, and skill shortages. Overall, the African continent progress towards a third reduction in premature mortality come 2030 is lagging behind. More can be done in the arena of effective policy implementation for risk factor reduction and CVD prevention, increasing health financing and focusing on strengthening primary health care services for prevention and treatment of CVDs, whilst ensuring availability and affordability of quality medicines. Further, investing in systematic country data collection and research outputs will improve the accuracy of the burden of disease data and inform policy adoption on interventions. This review summarizes the current CVD burden, important gaps in cardiovascular medicine in Africa, and further highlights priority areas where efforts could be intensified in the next decade with potential to improve the current rate of progress towards achieving a 33% reduction in CVD mortality.